Monetary power and vulnerability to sovereign debt crises: Rethinking the global financial architecture - Karina Patrício Ferreira Lima (Levy Economics Institute of Bard College, 2024)
This paper challenges the prevailing view in the sovereign debt literature by arguing that sovereign debt markets, in many respects, behave similarly to other credit markets. These markets are hierarchical rather than flat, inherently hybrid in nature, blending elements of public order and private markets, and regularly suffer from liquidity stress. Therefore, sovereigns, similarly to private actors in the market, are subject to liquidity stress and insolvency crises in a way that is integral to the global financial architecture. Critically, the legal and institutional design of the international monetary system exacerbates this stress. Structural asymmetries, notably the uneven distribution of monetary power, lead to liquidity stress being more pronounced in the periphery than at the apex or core of the system, rendering the former inherently more vulnerable to sovereign debt crises. The paper argues that such considerations should assume a central role in global policy discussions concerning the most appropriate mechanisms for addressing sovereign debt crises. It advocates for a reformed global financial architecture, emphasizing the necessity of a legally binding framework for sovereign debt restructuring that draws upon principles of corporate restructuring law, with the UK Companies Act 2006 (CA 2006) providing relevant analogies. This approach aims to ensure timely, equitable, and efficient restructuring processes, thereby confronting the challenges posed by the current ad hoc and often inequitable sovereign debt restructuring processes.
Keywords: 330; Sovereign Debt; Monetary Sovereignty; Monetary Power; Currency Hierarchy; Sovereign Debt Restructuring; International Monetary System; International Financial Architecture; Debt Service Suspension Initiative; Common Framework; Paris Club; China; Insolvency; Standstill; Cramdown; Moratorium